Efforts to Increase Mathematics Learning Activities and Achievements Through the Application of Game Methods in Class VI of SD Negeri 327 Sinunukan, Sinunukan District - Torang Siregar; Almira Amir (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research was carried out for 2 months using the game method in an effort to increase activity and mathematics learning performance for class VI students at SDN 327 Sinunukan, Sinunukan. The research was carried out in two cycles. The data collection technique is through observation sheets at each meeting by observers to see data about learning activities, while data about learning outcomes is obtained through daily test scores and student mathematics learning achievements in cycles 1 and 2. The results obtained from PTK through the game method model, show The increase in student activity results, especially in activities for preparing places, materials and tools, was 55.56%, activities for expressing ideas were 66.67%, activities for reading game rules and books were 74.04%. Based on student mathematics achievement data, the class average score in cycle I was 69.62, increasing to 73.51 in cycle II. The percentage of students who achieved the completion standard also increased in cycle I by 88.88% (Good Category), increasing to 100% (Special Category) in cycle II.